Iron ore modified with alkaline earth metals for the chemical looping combustion of municipal solid waste derived syngas. (1st February 2021) - Wang, Haiming; Liu, Guicai; Veksha, Andrei; Dou, Xiaomin; Giannis, Apostolos; Lim, Teik Thye; Lisak, Grzegorz
Abstract: The redox performances of iron ore (IO) modified with different alkaline earth metals (AEM) as oxygen carriers (OCs) were evaluated with thermogravimetric analysis (TGA) and fluidized bed reactor experiments for the chemical looping combustion (CLC) of municipal solid waste (MSW) derived syngas. AEM oxides (BaO, CaO, and MgO) and AEM aluminates (BaAl2 O4, CaAl2 O4, and MgAl2 O4 ) were systematically studied for their ability to promote the redox cycles performance of IO. Acid digestion, FESEM, and XRD analyses were conducted for the characterization of the OCs before and after redox reactions to investigate the promoting mechanism. It was found that the BaO-modified IO demonstrated the best reactivity with the reduction rate of 2.04%/min, which was twofold that of the pristine IO. AEM oxides presented superior redox performance than AEM aluminates owing to their strong interaction with Fe2 O3 with the formation of AEM ferrites. The formed CaFe2 O4 and MgFe2 O4 with spinel structure and BaFe12 O19 with hexagonal structure, as a result of the interaction, facilitated the lattice oxygen mobility and improved the reactivity of the modified IO. This interaction also increased the sintering resistance, while the morphology of the IO became more porous after redox cycles, which was also responsible for the improved performance during the long term CLC operation. Graphical abstract: Image 1 Highlights: Activity of iron ore was improved greatly with the loading of alkaline earth metals. Oxides showed better performance than aluminates in iron ore modification. Ferrites were formed due to the interactions between Fe and the loading oxides. Barium showed the best performance in improving the iron ore activity.